(3GdcaGjIs - (3eMeO Hf GdMSjf Hf eMeO Hf Nda GHf GdaQGA, CHh jYdj,J (B458 (3g` s
(3ChdgG (B:s
" (3aUd hGdbQV fhY ef GdSda hgh LGFR (B" s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B99 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B254s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B8 - (3U (B250 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1498s
Keywords: (3CUhd Gdabgs